ANALYSIS OF A RATIONAL EMOTIF BEHAVIOR THERAPY (REBT) APPROACH IN GROUP COUNSELING - Yuliani Pertiwi; Netrawati (Literasi Nusantara, 2021)
This article discusses the Rational Emotive Behavior Therapy (REBT) Approach in groups. Rational Emotive Behavior Therapy is a therapeutic design, in counseling, this application focuses on irrational thinking as a therapy goal, modification or changing beliefs which are various emotional and behavioral consequences. It can be concluded that REBT (Rational Emotive Behavior Therapy) is an approach that is able to change the thoughts and behavior of individuals who are irrational into rational ones. REBT counseling aims to improve and change the client's irrational attitudes, perceptions, ways of thinking, beliefs and views into rational ones, so that he can develop himself and achieve optimal self-realization. In addition, REBT aims to eliminate emotional disturbances such as: hate, fear, guilt, anxiety, anxiety, anger as a result of irrational thinking, and to train and educate clients to be able to face the realities of life rationally and generate confidence, values and values. values and abilities.